THE EXPERIENCE OF FOREIGN COUNTRIES IN THE DEVELOPMENT OF GENERAL CULTURAL COMPETENCIES OF PRESCHOOL EDUCATIONAL ORGANIZATIONS - Soliyev Ilhomjon Sobirovich; Shokirjonova Zuhraxon Murodjon qizi (Galaxy International Interdisciplinary Research Journal, 2024)
This article describes the opinions of foreign scientists about the development of the competencies of future teachers.Pedagogical skills and general competencies of the future pedagogue in the educational process were discussed.